Characterization and climate adaptation capacity of livestock farmers in two regions of Costa Rica - Cortés-Muñoz, Gerardo; Fuentes-Navarro, Eduardo; Mercado, Waldemar (Agronomía Mesoamericana, 2025)
Introduction. Dairy farms in Costa Rica have been classified into three production systems: specialized high-altitude, specialized lowland, and dual-purpose systems. However, this typification does not reflect their current complexity level, as there exists a wide variety of production systems based on sanitary, reproductive and feeding management practices. Objective. To characterize the dairy production systems in two representative livestock regions of Costa Rica and their technological adaptation capacities to climate change. Materials and methods. To determine the technical-productive, social, and economic characteristics of Costa Rican dairy farms located in the Chorotega and Huetar Norte regions, a designed and validated survey was applied. Data were collected between April and May 2021. A total of 143 farmers were interviewed, allowing for the evaluation of 193 variables. Subsequently, cluster analysis was performed, executing hierarchical cluster analysis, using Ward’s method. Results. Three clusters were obtained with farm management capacities: high, medium, and low, related to their climate change adaptation capacities. The first group comprised producers with higher education and farm management levels (high capacity), reflected in the adoption of more adaptation strategies. The farms of the second group (medium capacity), with lower technical management than the first group, and the third group of farms (low capacity), composed of producers with the lowest educational level, demonstrated a more limited technological management capacity. Conclusions. The livestock activity was characterized by three groups of producers with different climate change adaptation capacities.